On Stancu-Type Generalization of Modified p, q-Szász-Mirakjan-Kantorovich Operators. (9th January 2021) - Hu, Yong-Mo; Cheng, Wen-Tao; Gui, Chun-Yan; Zhang, Wen-Hui
Abstract : In the present article, we construct p, q -Szász-Mirakjan-Kantorovich-Stancu operators with three parameters λ, α, β . First, the moments and central moments are estimated. Then, local approximation properties of these operators are established via K -functionals and Steklov mean in means of modulus of continuity. Also, a Voronovskaja-type theorem is presented. Finally, the pointwise estimates, rate of convergence, and weighted approximation of these operators are studied.